2017
DOI: 10.1038/s41598-017-01141-4
|View full text |Cite
|
Sign up to set email alerts
|

The yeast osmostress response is carbon source dependent

Abstract: Adaptation to altered osmotic conditions is a fundamental property of living cells and has been studied in detail in the yeast Saccharomyces cerevisiae. Yeast cells accumulate glycerol as compatible solute, controlled at different levels by the High Osmolarity Glycerol (HOG) response pathway. Up to now, essentially all osmostress studies in yeast have been performed with glucose as carbon and energy source, which is metabolised by glycolysis with glycerol as a by-product. Here we investigated the response of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 52 publications
1
51
0
1
Order By: Relevance
“…3A), the only nonfermentable substrate in our study. Indeed, multiple studies that involve ethanol-grown yeast cultures in minimal media, used either a YPE medium (a standard YPD with ethanol instead of glucose) or a glycerol-ethanol mixture [21][22][23][24]. However, we did not change the conditions to be consistent with our single-molecule experiments.…”
Section: Resultsmentioning
confidence: 99%
“…3A), the only nonfermentable substrate in our study. Indeed, multiple studies that involve ethanol-grown yeast cultures in minimal media, used either a YPE medium (a standard YPD with ethanol instead of glucose) or a glycerol-ethanol mixture [21][22][23][24]. However, we did not change the conditions to be consistent with our single-molecule experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics of carbon source effect on glycerol production by C. orthopsilosis HH52: Data presented in Figure 3 showed that C. orthopsilosis HH52 could accumulate glycerol at variable concentrations using different carbons, the reason could be that various carbon sources used in fermentation might exhibit different degrees of osmotic pressure on the yeast cells (Leandro et al, 2011). Glycerol synthesis is essential for yeast cells to recompense an osmotic stress which is carbon source dependent (Ansell, 1997;Babazadeh et al, 2017). The current study indicated that the monosaccharides hexoses such as glucose and fructose exhibit the highest glycerol production yield.…”
Section: Screening and Identificationmentioning
confidence: 99%
“…Osmotolerance is lower upon growth on the less fermentable carbon source galactose accompanied by a reduced accumulation of glycerol (Vanacloig-Pedros et al 2015). Moreover, in the absence of a fermentable carbon source, yeast cells do no longer accumulate glycerol, and the adjustment of osmotic balance is further delayed (Babazadeh et al 2017). Taken together, we hypothesize that high salinity causes a nutritional stress in yeast cells, which is counteracted by different metabolic adjustments.…”
mentioning
confidence: 79%